Pengaruh era digitalisasi terhadap identitas nasional negara indonesia - Faruq, Basysyar Ahmad (Maliki Interdisciplinary Journal, 2025)
National identity is the basis and main foundation in building unity and togetherness of a nation, especially for a country like Indonesia that has a variety of ethnicities, cultures, languages, and natural diversity. In the midst of the digitalization era spearheaded by increasingly sophisticated technology and increasingly accessible information, the challenge of maintaining national identity will be even greater, given the influence of social media containing various kinds of information from various countries that can affect the cultural preferences of the Indonesian people and the lifestyle in the daily life of the Indonesian people. This article aims to examine the importance of understanding and applying the national identity that must always be maintained amidst sophisticated technology that displays cultural diversity from other countries. Using a qualitative approach, this research explains the concept of national identity, and its functions as a unifying tool and reminder of the national identity of Indonesian society, as well as the challenges that must be faced to maintain this identity. The results show that national identity contained in Pancasila plays a role as a unifying nation and the main foundation of Indonesian society in maintaining social stability, so it is necessary to empower national education, promote social culture, and instruct on the use of technology properly and correctly, in order to strengthen the foundation of national identity in the midst of diversity.